Streamer knotwilg branching: sudden transition in morphology of positive streamers in high-purity nitrogen. (5th August 2015) - Heijmans, L C J; Clevis, T T J; Nijdam, S; van Veldhuizen, E M; Ebert, U
Abstract: We describe a peculiar branching phenomenon in positive repetitive streamer discharges in high purity nitrogen. We name it knotwilg branching after the Dutch word for a pollard willow tree. In a knotwilg branching a thick streamer suddenly splits into many thin streamers. Under some conditions this happens for all streamers in a discharge at about the same distance from the high-voltage electrode tip. At this distance, the thick streamers suddenly bend sharply and appear to propagate over a virtual surface surrounding the high-voltage electrode, rather than following the background electric field lines. From these bent thick streamers many, much thinner, streamers emerge that roughly follow the background electric field lines, creating the characteristic knotwilg branching. We have only found this particular morphology in high purity nitrogen at pressures in the range 50 to 200 mbar and for pulse repetition rates above 1 Hz; the experiments were performed for an electrode distance of 16 cm and for fast voltage pulses of 20 or 30 kV. These observations clearly disagree with common knowledge on streamer propagation. We have analyzed the data of several tens of thousands of discharges to clarify the phenomena. We also present some thoughts on how the ionization of the previous discharges could concentrate into some pre-ionization region near the needle electrode and create the knotwilg morphology, but we present no final explanation.